First Time Up An Insider'S Guide For New Composition Teachers - Dethier, Brock (University Press of Colorado, 2005)
"First time up?"-an insider's friendly question from 1960s counter-culture-perfectly captures the spirit of this book. A short, supportive, practical guide for the first-time college composition instructor, the book is upbeat, wise but friendly, casual but knowledgeable (like the voice that may have introduced you to certain other firsts). With an experiential focus rather than a theoretical one, First Time Up will be a strong addition to the newcomer's professional library, and a great candidate for the TA practicum reading list. Dethier, author of The Composition Instructor's Survival Guide and From Dylan to Donne, directly addresses the common headaches, nightmares, and epiphanies of composition teaching-especially the ones that face the new teacher. And since legions of new college composition teachers are either graduate instructors (TAs) or adjuncts without a formal background in composition studies, he assumes these folks as his primary audience. Dethier's voice is casual, but it conveys concern, humor, experience, and reassurance to the first-timer. He addresses all major areas that graduate instructors or new adjuncts in a writing program are sure to face, from career anxiety to thoughts on grading and keeping good classroom records. Dethier's own eclecticism is well-represented here, but he reviews with considerable deftness the value of contemporary scholarship to first-time writing instructors-many of whom will be impatient with high theory. Throughout the work, he affirms a humane, confident approach to teaching, along with a true affection for college students and for teachers just learning to deal with them.